Analysis of LLDIKTI Region II Budget Implementation Performance Indicators (IKPA) for 2018-2020 Fiscal Year - Alwi Alwi (Journal of Indonesian Management, 2022)
The purpose of this study was to determine the comparison of the value of the LLDIKTI Wilayah II Budget Implementation Performance Indicator (IKPA) in 2018-2020. This type of research is comparative descriptive with the data collection method using secondary data taken from the application of the Ministry of Finance, specifically LLDIKTI Wilayah II. The results of this study indicate that LLDIKTI Wilayah II has made maximum efforts in implementing all performance indicators of budget implementation (IKPA). This can be seen from the achievements of IKPA which continue to increase, namely in 2018 amounting to 87.74. 2019 amounted to 91.76 and in 2020 an increase of 96.40. The achievement in 2020 is a special value for LLDIKTI Wilayah II, considering that this figure is considered very satisfying, besides that it is the biggest challenge in 2021 whether it can maintain this achievement or will it decrease otherwise. This requires special attention from all parties involved in budget management in order to further improve discipline, order and timeliness in budget management.